Rourkela-an example of co-operative development Aid - Klaus Röh (Intereconomics, 1966)
“The Observer”, London, reported last February to its readers on the Indian steel scenery the following: “The story of the three foreign steelworks in India is like an anecdote about a Russian, an Englishman and a German. At Bhilai, the Russians started with a roar of self-congratulation and are now a bit behind the times. The British at Durgapur were modest and their achievements are still modest. The Germans at Rourkela began in notorious muddle... and are now far and away the winners.” This is certainly a compliment to the achievements of the Rourkela steelworks for its now attained productivity and high profits. One should, however, not forget the many difficulties and shortcomings which the project had to face during its planning and construction phase. Mr. Klaus Röh has for one year personally studied the problems at the spot. His findings will shortly be published in a German monograph “Rourkela als Testfall”.
Keywords: 330